The Problems with Cross-Border Quality Assurance - Kinser, Kevin; Lane, Jason (International Higher Education, 2013)
Quality assurance for cross-border higher education often focuses on concerns about academic standards. But the challenge of evaluating international branch campuses and other foreign education outposts goes beyond enforcing basic standards of quality. We identify five issues that that make quality assurance in the cross-border context problematic.